Potentials of solar power plant in Waru Tua - Ain Sahara; Riza Hadi Saputra; A. M. Miftahul Huda (Universitas Ahmad Dahlan, 2020)
Penajam Paser Utara Regency is located on the coast of East Kalimantan Province. This regency has a huge solar resource potential, but the agreement in this regency still lacks electricity networks and can be resolved by the people in this regency still in dire need of electricity for street lighting, and daily electricity needs. One of them is in the village of Waru Tua, where this area is in great need of lighting in the dock area because it requires residents to make Aliving as a fisherman. Waru Tua really needs electricity for lighting at night Waru Tua Pier because it has to be a gathering place for residents before going to sea to prepare everything that must be prepared before going to sea. Discussing the research carried out examining the potential of solar power in Waru Tua. Based on existing considerations, and the potential proposed by the area, the method used is to measure the sunlight at Waru Tua Pier using Luxmeter, then the data is processed using the Simulink applicationin MATLAB to obtain the value of the amount of sunlight in the area, which is 16 KW with a total solar cell of 250 Wp.